2003
DOI: 10.1001/archderm.139.4.459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Subantimicrobial-Dose Doxycycline in the Treatment of Moderate Acne

Abstract: Objective: To determine if treatment with subantimicrobial-dose (SD) doxycycline hyclate (20-mg tablets taken twice daily) improved clinical outcome, had any detectable effect on skin flora, led to overgrowth or colonization of skin by opportunistic pathogens, or resulted in an increase in antibiotic resistance by the surface skin microflora in patients with moderate acne compared with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
142
0
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(158 citation statements)
references
References 14 publications
(22 reference statements)
5
142
0
11
Order By: Relevance
“…151 Importantly, some oral antibiotics, especially tetracycline derivatives, in addition to antibiotic activity against P acnes, exhibit certain antiinflammatory and immunomodulatory properties that may be operative in counteracting mechanisms or pathways involved in acne lesion development. 60,[153][154][155] Typically, 4 to 8 weeks of compliant oral antibiotic use are needed before the clinical effects of an oral antibiotic are visible, whereas maximal response may require 3 to 6 months of administration. 15,70 Once the formation of new inflammatory lesions, defined as lesions that are raised by palpation, are markedly diminished in number, consideration may be given to stopping oral antibiotics with continuation of topical therapy to maintain control of acne.…”
Section: Adding An Oral Antibioticmentioning
confidence: 99%
“…151 Importantly, some oral antibiotics, especially tetracycline derivatives, in addition to antibiotic activity against P acnes, exhibit certain antiinflammatory and immunomodulatory properties that may be operative in counteracting mechanisms or pathways involved in acne lesion development. 60,[153][154][155] Typically, 4 to 8 weeks of compliant oral antibiotic use are needed before the clinical effects of an oral antibiotic are visible, whereas maximal response may require 3 to 6 months of administration. 15,70 Once the formation of new inflammatory lesions, defined as lesions that are raised by palpation, are markedly diminished in number, consideration may be given to stopping oral antibiotics with continuation of topical therapy to maintain control of acne.…”
Section: Adding An Oral Antibioticmentioning
confidence: 99%
“…Doxycycline when used alone or in combination with Benzoyl peroxide has retained its efficacy, and the efficacy is greater when combined with topical benzoyl peroxide. 13 Clindamycin either alone or in combination with topical benzoyl peroxide 5% cream shows greater efficacy than doxycycline either alone or in combination with topical benzoyl peroxide 5% cream. The reason for lesser efficacy of doxycycline could be due to development of resistance by propionibacterium acne in some of the patients included in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…31 Dosing of Doxycycline in acne vulgaris has become another interesting area of research since the drug was found to be significantly effective in few occasions even at a sub antimicrobial dose level (20mg twice daily) while treating moderate facial acne cases. 32,33 A very recent study with larger sample size has shown that a modified release sub antimicrobial dose of Doxycycline (40mg once daily) was not only effective as 100mg daily dose but also appeared better in terms of safety in the treatment of moderate to severe inflammatory acne. 34 Lately, an in vitro study focusing the anti-inflammatory property of Doxycycline also indicated that the drug could be safely used at a low dose (20-40mg daily) in chronic or acute skin diseases where inflammation has to be controlled or prevented.…”
Section: Discussionmentioning
confidence: 99%